Revascularization of a Permanent Tooth with Necrotic Pulp and Apical Periodontitis - Saad W; Almaslamani M; Saleh AR (Dove Medical Press, 2024)
Wala Saad,1 Manal Almaslamani,2 Abdul Rahman Saleh2 1Department of Clinical Sciences, College of Dentistry, Ajman University, Ajman, United Arab Emirates; 2Department of Clinical Sciences, Center of Medical and Bio-Allied Health Sciences Research, College of Dentistry, Ajman University, Ajman, United Arab EmiratesCorrespondence: Manal Almaslamani, Department of Clinical Sciences, Center of Medical and Bio-Allied Health Sciences Research, College of Dentistry, Ajman University, Ajman, United Arab Emirates, Email m.almaslamani@ajman.ac.aeAbstract: This case report details a pulp revascularization treatment administered to a mature permanent tooth exhibiting pulp necrosis. A 22-years old female patient complained of the recurrence of a sinus tract labial of the maxillary right central incisor; which was tender on biting. Diagnosis of pulp necrosis and symptomatic apical periodontitis. Preoperative periapical and CBCT radiographs showed root with wide apical foramen and large apical radiolucency. Pulp revascularization procedure was performed using 1.3% sodium hypochlorite irrigation, 17% Ethylenediaminetetraacetic acid irrigation, and calcium hydroxide intracanal dressing for 2 weeks. During the last visit, intentional bleeding was induced, collagen matrix was set over the blood clot, 2 mm of mineral trioxide aggregate and glass-ionomer filling was placed. A year of follow-up, the tooth showed no signs or symptoms and responded normally to the sensibility tests. Intra-oral periapical radiograph and the CBCT showed significant reduction in the periapical lesion's size, slight reduction in the apical foramen's size, and hard radiopaque material deposition at the root's middle third.Keywords: pulp revascularization, pulp regeneration, open apex, necrotic pulp, apical periodontitis